Questionnaire Design in Short Message Service (SMS) Surveys. Issue 3 (August 2019) - Lau, Charles Q.; Sanders, Herschel; Lombaard, Ansie
Short message service (SMS or text messaging) surveys can collect data quickly and inexpensively. However, SMS surveys have space constraints that pose difficulties to questionnaire designers: Questions can only be 160 characters or less, surveys must be short, and many respondents use phones with small screens. In this article, we compare SMS and benchmark face-to-face surveys across four African countries to address three common questions in SMS questionnaire design. First, are multiple response questions feasible? Second, is it necessary to randomize response option order? Third, should "don't know" response options be included? Our results provide practical guidance about how to improve data quality with this emerging mode of data collection.